2018
DOI: 10.1002/fsn3.594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incorporation of soy flour on functional, nutritional, and sensory properties of mushroom–moringa‐supplemented healthy soup

Abstract: The research study was conducted to evaluate the effect of soy flour on functional, nutritional, and sensory properties of mushroom–moringa‐supplemented soup which could be used as a protein‐supplemented ready‐to‐eat food. In this study, corn flour was supplemented with soy flour at different levels such as 20% (T4), 15% (T3), 10% (T2), and 5% (T1), and without soy flour was kept as control (T0). Fixed amount of mushroom and moringa leaf powder was added in all soup powders. Soup powders were analyzed for func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
6
13
0
Order By: Relevance
“…Some authors use soy flour to enhance the nutritional value of different foods, reporting exchanges ranging from 5% to 40% to make specific recipes such as bread, 14 tortillas, 15 biscuits, 16 fritters, 17 garri, 18 and soup. 19 In any of these publications, exchange of soy flour for other main ingredients in less than 10% of weight did not modify the acceptability of the food. In this study, we simulated replacing a small amount of rice (10 g) with 10 g of either TSP, soy flour, or tofu, which represents 13% of the rice and 4% of the total recipe by weight.…”
Section: Resultsmentioning
confidence: 91%
“…Some authors use soy flour to enhance the nutritional value of different foods, reporting exchanges ranging from 5% to 40% to make specific recipes such as bread, 14 tortillas, 15 biscuits, 16 fritters, 17 garri, 18 and soup. 19 In any of these publications, exchange of soy flour for other main ingredients in less than 10% of weight did not modify the acceptability of the food. In this study, we simulated replacing a small amount of rice (10 g) with 10 g of either TSP, soy flour, or tofu, which represents 13% of the rice and 4% of the total recipe by weight.…”
Section: Resultsmentioning
confidence: 91%
“…Akubor and Onimawo (2003), similarly reported higher WAC in maize flour enriched with soybean flour. According to Mohajan, Orchy, and Farzana (2018), proteins are capable of binding large quantities of water due to their ability to form hydrogen bonds between water molecules and polar group on the polypeptide chain. Differences in starch content, starch composition (i.e., amylose content) as well starch granular structure may also explain the variation in WAC (Falade & Oyeyinka, 2015).…”
Section: Flour Functionalitymentioning
confidence: 99%
“…Other authors have shown that acceptance of mushroom addition to a meat patty is both a function of amount of mushroom added and culture, with higher levels being acceptable by Korean consumers and lower levels accepted by U.S. consumers [26]. Various authors have examined sensory properties of specific mushrooms added to food products e.g., [25][26][27][28][29] but many of those studies focused on consumer acceptance rather than flavor properties. Moliszewska [30] provided a review of some specific aroma notes found in a few mushroom varietals and related some of those notes to chemical compounds present in those particular mushrooms.…”
Section: Introductionmentioning
confidence: 99%